2023
DOI: 10.1101/2023.07.27.23293177
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multimodal Molecular Imaging Reveals Tissue-Based T Cell Activation and Viral RNA Persistence for Up to 2 Years Following COVID-19

Michael J. Peluso,
Dylan Ryder,
Robert Flavell
et al.

Abstract: The etiologic mechanisms of post-acute medical morbidities and unexplained symptoms (Long COVID) following SARS-CoV-2 infection are incompletely understood. There is growing evidence that viral persistence and immune dysregulation may play a major role. We performed whole-body positron emission tomography (PET) imaging in a cohort of 24 participants at time points ranging from 27 to 910 days following acute SARS-CoV-2 infection using a novel radiopharmaceutical agent, [18F]F-AraG, a highly selective tracer tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…6 More recently, an autopsy study showed widespread sub-genomic RNA in tissues of decedents up to 6 months post-COVID, 7 and we have reported SARS-CoV-2 spike RNA detection in gut biopsies for up to 2.5 years post-COVID. 9 SARS-CoV-2 antigens, particularly spike protein and its components, are known to be highly immunogenic. 1416 These antigens have been shown to induce inflammatory cytokine responses as well as dysregulation of fibrinogen, complement proteins, and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 More recently, an autopsy study showed widespread sub-genomic RNA in tissues of decedents up to 6 months post-COVID, 7 and we have reported SARS-CoV-2 spike RNA detection in gut biopsies for up to 2.5 years post-COVID. 9 SARS-CoV-2 antigens, particularly spike protein and its components, are known to be highly immunogenic. 1416 These antigens have been shown to induce inflammatory cytokine responses as well as dysregulation of fibrinogen, complement proteins, and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…5 For example, viral RNA or protein persistence has since been identified in a variety of tissues in gut biopsy and autopsy studies for up to 2 years post-infection, although the clinical significance is unclear. [6][7][8][9] Recent studies assessing protein and RNA in plasma reported antigen detection in small cohorts of individuals post-COVID, 10,11 but their conclusions were limited by sporadic detection at or near the assay quantification limit and a lack of comparison to a large number of true negative control samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Recent studies suggest viral persistence in a subset of individuals with PASC, including prolonged gastrointestinal shedding, ongoing Spike and Nucleocapsid antigen in neuronal and astrocytic exosomes, and evidence of persistent viral RNA or proteins in deep tissues and plasma. [5][6][7][8][9][10] Among high-risk, unvaccinated, nonhospitalized individuals with symptomatic COVID-19, nirmatrelvir, a novel orally-administered SARS-CoV-2 main protease (M pro ) inhibitor in combination with ritonavir reduces viral load and progression to severe disease. 11 Anecdotal reports suggest that nirmatrelvir may improve Long COVID symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Higher acute viral load or prolonged shedding may be associated with increased risk 3,4 . Recent studies suggest viral persistence in a subset of individuals with PASC, including prolonged gastrointestinal shedding, ongoing Spike and Nucleocapsid antigen in neuronal and astrocytic exosomes, and evidence of persistent viral RNA or proteins in deep tissues and plasma 5–10 …”
Section: Introductionmentioning
confidence: 99%